Captiva - White, Randy Wayne (G.P. Putnam's Sons, 2018)
An environmental war breaks out in Florida between sports fishermen and commercial fishermen who are despoiling the waters. With friends in both camps Doc Ford, a government agent turned marine biologist, prefers to stay neutral. But a man's death in the explosion of a jetty brings him into it all the same. By the author of The Man Who Invented Florida.